Hydrophobic/Hydrophilic Interplay in 1,2,4‐Triazole‐ or Carboxylate‐Based Molybdenum(VI) Oxide Hybrids: A Step Toward Development of Reaction‐Induced Self‐Separating Catalysts - Lysenko, Andrey B. (2022)
2-(4H-1,2,4-triazol-4-yl)acetic acid (trglyH) and (dl)-4-methyl-2-(4H-1,2,4-triazol-4-yl)pentanoic acid (trleuH) were used as ligands for the development of MoO3 coordination hybrids for catalytic applications. Coordination polymers [Mo2O6(Htrgly)] ·H2O (1) and [MoO3(trleuH)] · 0.5H2O (2) were prepared and structurally characterized. Compound 1 adopts a structure in which edge-sharing MoO6 octahedra are organized in a ribbon motif via μ3-O bridges. The Htrgly ligand exists as a zwitterion: - CO2- links two Mo(VI) in a μ2-η1 : η1 mode, while positively charged triazolium is left uncoordinated. In 2, Mo atoms are joined in a chain through μ2-O. The more hydrophobic trleuH appears in a nonionized form and its [N- N] sites serve as a “clamp” for supporting the [-OMo(O)2-OMo(O)2(tr)2]n sequence. The complexes were explored for liquid phase catalytic epoxidation of cis-cyclooctene, using H2O2 or tert-butylhydroperoxide as oxidants. The hybrids showed good catalytic activity, and 2 behaved as a reaction-induced self-separating catalyst for olefin epoxidation with H2O2, presenting advantages of homogeneous and heterogeneous catalysis .